Being Dialogic with the Pragmatic Literacies of Late Medieval England. (25th October 2018) - Salter, Elisabeth
Abstract: This article uses last will and testaments from several regions of England as a major source of evidence for the ways that the majority of medieval people used written text in the formation of communities of interpretation. In so doing it examines encounters with texts that must have informed medieval people's understandings of the English language, including the nuances of meaning that English could provide in a society that was still employing Latin for many official communications. These encounters are understood to be dialogic in a number of ways and the author's interaction with the evidence of these encounters is also understood to be a dialogic process. A premise of this article is that an administrative document such as the last will and testament must be understood as a major source of contact with the written word for the non-elite people of late medieval England. This is an association with written text – both vernacular and Latin – described as 'pragmatic literacy' by Michael Clanchy in his formative work on the interactions between orality, literacy, and memory in the high and late middle ages. A key proposition, therefore, is that if we are to understand more about the ways that the majority of people interacted with and interpreted 'English' (i.e. literature) in this era, then we need to consider administrative documents such as the last will and testament, and the uses of these pragmatic literatures.